2015
DOI: 10.1080/1743873x.2014.985226
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing colonial tea heritage through historic lodging

Abstract: A number of types of lodging and leisure facilities were associated with the colonial tea industry in Ceylon (today Sri Lanka), including clubs for the planters' and the houses and bungalows of the managers and staff on the tea estates. Today some of these built heritage remains of the tea industry have been repurposed as heritage lodgings for tourists. Taking as a case study the tea-producing hill country of Sri Lanka, this paper identifies the heritage accommodations related to the legacy of the tea industry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…From supply perspective, literature suggests that there are many links between tea farming and sales and tourism resources, such as sites and locations, historical buildings, gardens, tea fields (production and processing), and tea sales outlets [10,[55][56][57]. Tea resources/assets also include tea cultural activities, such as visiting tea fields, factories, and houses, experiencing tea drinking customs, tea purchases, etc.…”
Section: Tea Assets/resources and Offeringmentioning
confidence: 99%
See 1 more Smart Citation
“…From supply perspective, literature suggests that there are many links between tea farming and sales and tourism resources, such as sites and locations, historical buildings, gardens, tea fields (production and processing), and tea sales outlets [10,[55][56][57]. Tea resources/assets also include tea cultural activities, such as visiting tea fields, factories, and houses, experiencing tea drinking customs, tea purchases, etc.…”
Section: Tea Assets/resources and Offeringmentioning
confidence: 99%
“…More specifically, the findings by Gunasekera and Momsen [55], Jolliffe and Aslam [56], and Su et al [13] suggest the main issues, aims, and conditions from the perspective of managing the development process and formulation of strategic aims [9,62]. The suggestions and recommendations by Jolliffe [10], Aslam and Jolliffe [57], and Star et al [64] were also confirmed regarding the management strategies and various actions enhancing to achieve a sustainable development and management of the two pillars-tea and tourism-of local economy. Likewise, the experiential nature of tea tourism activities was equally conformed by participants stakeholders, a finding highlighted by Fusté-Forné [11], Gunasekera and Momsen [55], and Star et al [64] indicating that these projects should be planned, designed, and provided in an integrated fashion [6,26].…”
Section: Main Findingsmentioning
confidence: 99%
“…The most celebrated form of agritourism in the region is tea cultivation, with its associated plantation landscapes, colonial and postcolonial infrastructure, processing centers, and retail outlets. This is especially popular in central Sri Lanka and the northeastern states of India (Aslam & Jolliffe, 2015;Jolliffe, 2007;Jolliffe & Aslam, 2009).…”
Section: Traditional Livelihoodsmentioning
confidence: 99%
“…In such a situation, the increasing number of tourist arrivals leads to an increase in household income for the local communities. Developing countries are blessed with tourism resources which can create wealth among the local people, such as the beaches in Costa Rica (Duim & Caalders 2008), the tea heritage tourism in Sri Lanka (Aslam & Jolliffe 2015), and cultural tourism in Mae Hong Son province of northern Thailand (Lacher & Nepal 2010).…”
Section: And Mycite Indexesmentioning
confidence: 99%